Interactive Museum Tours: A Guide to In-Person and Virtual Experiences - Vatsky, Sharon (Rowman & Littlefield Publishers, 2023)
This easy-to-follow yet comprehensive book provides everything an educator working in a school or museum, in person or online, needs to develop experiences that encourage close looking, spark the imagination, and support the development of critical thinking skills. Sharon Vatsky looks at the entire tour experience including planning, facilitation, and reflection. By providing a flexible tour-planning template – jointly developed by the education departments of the Guggenheim Museum, Metropolitan Museum of Art, Museum of Modern Art and Whitney Museum of American Art, this book clearly articulates strategies and advice for the educator who wants to facilitate inquiries that encourage participants to think together and think deeply. To demonstrate the flexibility and adaptability of the tour planning template, museum educators with deep experience specializing in working with diverse audiences share how they adjust the tour planning template to accommodate the attributes and strengths of the visitors they work with most closely. These accommodations to the template include ways to support family learning, school tours, virtual tours, promote social and emotional learning, work effectively with students with autism, adults with low vision and blindness and adults with Alzheimer’s disease and other dementias. These contributions are included to demonstrate that the tour planning template can be adjusted to support the varied abilities and learning styles of multiple audiences. Features include: An insider’s guide to tour planning featuring advice and strategies from museum educators across the U.S. A tested tour planning template that is adaptable and flexible for multiple audiences How to identify tour themes that work… and those that don’t What makes for effective object selection and sequencing How to encourage and facilitate productive discussions Inserting the right factual and contextual information at the right time Multi-modal activities for in-person and online participation Adapting your tour plans for varied audiences, including families, school groups, virtual groups and more…